2011
DOI: 10.5194/acp-11-1295-2011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the CALIPSO Lidar 532 nm attenuated backscatter calibration using the NASA LaRC airborne High Spectral Resolution Lidar

Abstract: To better assess the range of conditions under which CALIOP data products are produced, these validation flights were conducted under both daytime and nighttime lighting conditions, in multiple seasons, and over a large range of latitudes and aerosol and cloud conditions. This paper presents a quantitative assessment of the CALIOP 532 nm calibration (through the 532 nm total attenuated backscatter) using internally calibrated airborne HSRL underflight data and is the most extensive study of CALIOP 532 nm calib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 34 publications
3
88
0
Order By: Relevance
“…CALIOP's attenuated backscatter shows a very small negative bias relative to AHSRL both at nighttime (−2.7 % ± 2.1 %) and daytime (−2.9 % ± 3.9 %) but lies within the uncertainties of AHSRL (Rogers et al, 2011). No seasonal, latitudinal or vertical dependencies were found.…”
Section: Space-borne Caliop Lidarmentioning
confidence: 83%
See 2 more Smart Citations
“…CALIOP's attenuated backscatter shows a very small negative bias relative to AHSRL both at nighttime (−2.7 % ± 2.1 %) and daytime (−2.9 % ± 3.9 %) but lies within the uncertainties of AHSRL (Rogers et al, 2011). No seasonal, latitudinal or vertical dependencies were found.…”
Section: Space-borne Caliop Lidarmentioning
confidence: 83%
“…Daytime retrievals are less accurate than nighttime retrievals because they are affected by the noise from scattering of solar radiation in the field of view of the detector Rogers et al, 2011). Daytime retrievals thus have a higher backscatter sensitivity threshold (∼0.5 Mm −1 sr −1 at sea level) compared to nighttime retrievals (∼0.4 Mm −1 sr −1 ).…”
Section: Space-borne Caliop Lidarmentioning
confidence: 99%
See 1 more Smart Citation
“…Through extensive comparisons between CALIOP and the airborne NASA Langley Research Center High Spectral Resolution Lidar, Rogers et al (2011) have demonstrated the high accuracy of CALIOP's 532 nm attenuated backscatter calibration, finding that total attenuated backscatter from the two instruments agrees within 2.7 % ± 2.1 % at night and 2.9 % ± 3.9 % during the day. Other studies have also found good agreement between CALIOP and ground-based lidar measurements (e.g., Mamouri et al, 2009;Mona et al, 2009).…”
Section: Satellite Observationsmentioning
confidence: 99%
“…However, the stratospheric backscatter signal is weak and requires averaging of only the nighttime measurements over several days and typically 0.5 km vertically and 500 km horizontally (Vernier et al, 2011b). Additionally, the uncertainty in the calibration with respect to the molecular background that is on the order of the stratospheric aerosol signal leads to a potential bias in the stratospheric measurements (Rogers et al, 2011). CALIPSO was launched in 2006, and although it is presently still operational it is also operating beyond its design lifetime.…”
Section: Introductionmentioning
confidence: 99%